ARUS PASANG SURUT SEBAGAI PEMBANGKIT ENERGI LISTRIK DI PERAIRAN MUARA SUNGAI MESJID DUMAI RIAU - Musrifin ' (Fakultas Perikanan dan Kelautan, Universitas Riau, 2009)
Tidal range and tidal current in Sungai Mesjid Estuary have been analyzedin order to find out whether the tidal power in this area could be generated theelectricity. Observations conducted at the end of 2007 and early 2008. Maximumtidal height was 2.8 m and current velocity 0.05 – 0.49 m/s. The tidal type ismixed predominantly semidiurnal tide, flood and ebb tide occur twice a day.Tidal energy conversion (TEC) for low current velocity has been designed.Low tidal current could generated electricity 7.72 Watts and high tidal currentable to generate 78.76 Watts. There was a positive correlation between tidalcurrent velocity and voltages as well as electric power.